A constituição identitária do sujeito-consumidor: consumo colaborativo, comunicação e atribuição de sentidos na cultura do consumo contemporânea - Borges, Carlise Nascimento (2021)
This thesis research object is the consumer-subject's identity constitution from the meanings attributed to collaborative consumption practices emerging in the second decade of the 21st century. Under the approach of historical dialectical materialism (MARX 1982 apud NETTO, 2011), the phenomenon entitled “collaborative consumption” (ALONSO, 2017; BELK, 2014a, 2014b; BOTSMAN; ROGERS, 2001; RIFKIN, 2016) is interpreted in this study as an empirical excerpt of the countless practices (particularities) existing in the concrete reality (totality) researched – the contemporary consumption culture (ALONSO, 2005; FONTENELLE, 2017; SLATER, 2002), which is based on flexible accumulation capitalism (HARVEY, 2008; SENNET, 2006). Assuming a relational-praxiological perspective of communication (FRANÇA, 2003, 2016) and consumption as a producer of meanings (BACCEGA, 2011; DOUGLAS; ISHERWOOD, 2013; GARCÍA CANCLINI, 1999; McCRACKEN, 2003, 2007; ROCHA, 2005), this research aims to understand how the meanings attributed by the consumersubject to collaborative consumption practices are articulated to their identity constitution in the contemporary consumption culture. To this, three qualitative researches were developed throughout this thesis: a) a bibliographic research, with the purpose of supporting theoreticalconceptual assumptions and identifying consumption culture transformations as their relation with the consumer-subject constitution; b) a systematic literature review on qualitative synthesis, to problematize conceptions regarding collaborative consumption; c) a field research, using “episodic interviews” (FLICK, 2002, 2004) as a method, in order to survey situations and experiences around collaborative consumption practices, investigating the meanings that emerge. Elements of the french discourse theoretical analysis (BACCEGA, 1995, 1998; CHARAUDEAU, 2013, 2017; ORLANDI, 2001) were used as devices for analyzing the narratives collected in the interviews. The identity constitution depends on a relational process (a social dimension) and happens since the articulation of meanings (a symbolic dimension) (DUBAR, 2006; GIDDENS, 2002; WOODWARD, 2000). Based on their daily consumption choices, the consumer-subject becomes a receiver of significant properties from the “goods” he/she consumes, incorporating them into their identity (BACCEGA, 2011; SLATER, 2002). In this context, the research results reveal that practices that prioritize “dematerialized” (SLATER, 2002) or “experience” (PEREIRA; SICILIANO; ROCHA, 2015) consumption and that contribute to a more “conscious” consumption (ALONSO, 2017; FONTENELLE, 2017) assume, in the minds of the interviewees, a sense of “correct consumption”. In contrast, “material consumption” (of tangible goods) is condemned as consumerism (ROCHA, 2005), which presents itself as “incorrect consumption”. The “correct consumption” is associated with the figure of the “hero-consumer” – an identity project (CASTELLS, 2018) that represents a “natural evolution”, a “right destination” to be reached by the consumer-subject in contemporary times.